Evaluation of the Effects of Ultra-Low Dose Naloxone on Brachial Plexus Block with Bupivacaine - Bhattarai, Amit Sharma; Shrestha, Gentle Sunder; Koirala, Megha; Shrestha, Pramesh Sunder; Marhatta, Moda Nath (Birat Journal of Health Sciences, 2021)
Introduction: Adjuvants are used in conjunction with local anaesthetics for brachial plexus block to quicken onset, prolong duration and augment the quality of anaesthesia.Objectives: The study aims to evaluate the effect of adding ultra-low dose naloxone to bupivacaine on the duration of postoperative analgesia.Methodology: A prospective, randomized, double-blind study was conducted including forty American Society of Anesthesiologists Physical Status (ASA PS) I and II patients of either sex between 15 and 65 years of age scheduled for upper limb surgery. They were randomized into two groups. Group BN received a mixture of 0.33% plain bupivacaine with ultra-low dose naloxone (100 ng) and group BS received 0.33% plain bupivacaine with saline. The procedure was standardized in both groups. The onset of sensory and motor block were assessed with pinprick sensation and muscle power respectively. Visual Analogue Score (VAS) was used to assess the pain at 1, 2, 4, 8 and 12 hours postoperatively.Result: The patients were comparable with respect to age, sex, ASA PS, baseline hemodynamic and respiratory parameters and duration of surgery. The mean duration of analgesia in group BN was significantly longer (610.7±125.4 mins) as compared to group BS (354.3±59.6 mins) (p